The Impact of Early Marriage In The Perspective of Maqashid Syariah: A Systematic Literature Review - Afra Aulia Hesasy, Salsabila; Yunika Triana (Muhammadiyah University of Surabaya, 2025)
Early marriage is a phenomenon that must be prevented because it has the potential to deprive children of their rights, such as the right to protection from discrimination, the right to education, the right to health, and social rights. The main drivers of early marriage include economic, religious, parental, and environmental factors. Early marriage has various consequences and impacts that are detrimental to personal well-being. This study used a systematic literature review method by taking data from Scopus and found 9 articles relevant to the research topic. The results showed that the impacts of early marriage on children include interruption of education, low economic status, stress, and the risk of maternal and child mortality. Therefore, the impact of early marriage is not in line with the principles of maqashid sharia which upholds human welfare. This study aims to determine the impact of early marriage and reveal that early marriage is not in line with the principles of maqashid sharia. The principles of maqashid sharia are protecting the mind (hifdz al-aql), protecting the soul (hifdz an-nafs), and protecting property (hifdz al-mal). In addition to discussing the impacts of early marriage and observing maqashid sharia, this study also provides recommendations for preventing early marriage. Keywords: Early Marriage, Impact of Early Marriage, Maqashid Sharia, Maslahah.